Biogas generation from Sorghum bicolor stalk: Effect of pretreatment methods and economic feasibility - S. O. Dahunsi; A. T. Adesulu-Dahunsi; C. O. Osueke; Adedoyin Isola Lawal; T. M. A. Olayanju; J. O. Ojediran; J. O. Izebere (Energy Reports, 2019)
In this study, biogas was produced from the anaerobic digestion of Sorghum bicolor stalk. Pretreatment of the biomass was carried out prior to the digestion using sulfuric acid ( H2SO4) and hydrogen peroxide (H2O2). The physicochemical, elemental and structural analyses were carried out on the biomass before and after pretreatment. The microbial composition of the fermenting materials were also determined using standard method while the Fourier Transform Infra-red (FTIR) spectroscopy were used to quantify the structural changes that took place after pretreatments. Results showed enormous reduction of hemicellulose and partial solubilization of cellulose with the application of H2SO4 for pretreatment with obvious breakdown of all important bonds in the biomass. The most suitable condition for the most efficient acidic pretreatment of the Sorghum bicolor stalk was using H2SO4 concentration of 0.75% (v.v-1), autoclave temperature of 118~°C and biomass dry mass of 3.7 g for 52 min. However, the use of H2O2 caused huge solubilization of lignin while partial dissolution of hemicellulose took place. The most suitable condition that gave the best result in this pretreatment procedure was H2O2 concentration of 6.8% (v.v -1), shaker temperature of 28~°C, agitation at 126 rpm and 3 g of biomass for 85 min. Overall, the use of the H2O2 showed reduction of lignin and hemicellulose by 73 and 42% respectively while also increasing the concentration of cellulose by 23%. The acid and alkaline pretreated biomass produced a total of 312.3 and 607.1 LNbiogas.kg VSad -1respectively. In comparison, the biomass pretreated with H2O2 produced 65% more LNbiogas.kg VSad-1 than the other and equally reduced the production time by 5 days. For the alkaline treated biomass, the 1422 kWh t-1 TS thermal energy gain exceeded the 945 kWh t-1 TS used in the pretreatment thus giving a net thermal energy of 477 kWh t-1 TS. However, the acidic pretreatment of Sorghum bicolor stalk is not profitable because the -131 kWh t-1 TS thermal energy gain was far below the 1025 kWh t-1 TS thermal energy used in pretreatment with a net thermal energy of -761 kWh t-1 TS. Till now, use of low-cost H2O2 for biomass pretreatment is unpopular while the uses of other strong alkali and acids are well studies. However, hydrogen peroxide gave better product yield. Therefore, use of this alkali pose a novel biotechnological means for generating biogas.
Keywords: 330; Biogas; Biomass; Economics; Energy; Optimization; Pretreatment